Institutional Quality and International Trade - Levchenko, Andrei (Washington, D.C. : International Monetary Fund, 2004)
The quality of institutions-meaning the quality of contract enforcement, property rights, shareholder protection, and the like-has received a great deal of attention in recent years. The purposes of this paper are twofold. First, it studies the consequences of trade when institutional differences are the source of comparative advantage among countries. Institutional differences are modeled within the Grossman-Hart-Moore framework of contract incompleteness. It is shown, among other things, that the less developed country may not gain from trade, and that factor prices may actually diverge as a result of trade. Second, the paper provides empirical evidence of "institutional content of trade:" institutional differences are shown to be important determinant of trade flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet